Pharmacokinetics of high-dose nebulized amikacin in ventilated critically ill patients. (11th August 2016) - Petitcollin, A.; Dequin, P.-F.; Darrouzain, F.; Vecellio, L.; Boulain, T.; Garot, D.; Paintaud, G.; Ternant, D.; Ehrmann, S.
Abstract : Background: Antibiotic nebulization theoretically allows the delivery of high doses to the lungs together with limited systemic exposure and toxicity. This study aimed to describe amikacin pharmacokinetics, and especially its absorption, in patients treated with high-dose nebulized amikacin. Patients and methods: Twenty critically ill patients experiencing ventilator-associated pneumonia received a 20 mg/kg infusion of amikacin, followed by either three other infusions or three nebulizations of 60 mg/kg amikacin. An extensive sampling regimen allowed measurement of amikacin serum concentrations at 0.5, 1, 1.5, 2, 3, 4, 6, 10 and 24 h after each administration. Amikacin pharmacokinetics was studied by population compartmental modelling. Results: Amikacin pharmacokinetics was best described using a two-compartment structural model with first-order distribution and elimination, in which lung absorption was described using a transit model. Estimated means (interindividual variability) of the main parameters were: bioavailability F = 2.65% (22.1%); transit compartments n  = 1.58 (fixed); transit constant k tr  = 1.38 h −1 (33.4%); central volume V c  = 10.2 L (10.5%); and elimination constant k 10  = 0.488 h −1 (35.8%). The addition of interoccasion variability on F (44.0%) and k 10 (41.7%) allowed the description of intraindividual variability of bioavailability and elimination. Amikacin clearance was positively correlated with baseline creatinine clearance. Conclusions: Our pharmacokinetic model provided an accurate description of amikacin concentrations following nebulization. There was wide interindividual and interoccasion variability in the absorption and elimination of amikacin. Nevertheless, systemic exposure after nebulization was always much lower than after infusion, an observation suggesting that nebulized high doses are safe in this regard and may be used to treat ventilator-associated pneumonia.